The Relationship Between Diabetes Self-Management Education and Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Probosiwi, Neni; Siswidiasari, Arifani (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels, which can cause serious damage to the heart, blood vessels, kidneys, eyes, and nerves. This study aimed to determine the relationship between diabetes self-management education and blood glucose levels in patients with type 2 diabetes mellitus at the Balerejo Public Health Center. This study used an observational analytical study with a cross-sectional design using consecutive sampling. Data were collected prospectively and analyzed using Spearman's Rank Test on 50 patients. The results of the analysis of the diabetes self-management education questionnaire, in the domain of diet with a good category of 32 people (64%), physical exercise 8 people (16%), foot care 34 people (68%), drug therapy 34 people (68%), and glucose level monitoring 17 people (34%). The blood glucose level values ​​​​in the normal range are GDP 21 people (42%), GD2PP 27 people (54%), HbA1c 20 people (40%), and lipid profile values ​​​​of total cholesterol 27 people (54%), LDL 28 people (56%), HDL 29 people (58%), triglycerides 27 people (54%). The results of the Spearman Rank analysis showed that there was a relationship between diabetes self-management education with GDP p-value 0.022; r 0.32, G2PP p-value 0.004; r 0.4, HbA1c p-value 0.036; r 0.3, total cholesterol p-value 0.027; r 0.31, LDL p-value 0.015; r 0.34, HDL p-value 0.008; r 0.37, triglyceride p-value 0.004; r 0.4. Conclusion: There is a significant relationship between diabetes self-management education and blood glucose levels as well as lipid profiles.